Organic additives used in beef cattle feedlot: Effects on metabolic parameters and animal performance - Leite, Rhaony Gonçalves [UNESP]; Romanzini, Eliéder Prates [UNESP]; Delevatti, Lutti Maneck [UNESP]; Hoffmann, Alvair [UNESP]; Ferrari, Adriana Cristina [UNESP]; D'Aurea, André Pastori; Fernandes, Lauriston Bertelli; Oliveira, Amanda Prates; Reis, Ricardo Andrade [UNESP] (Wiley, 2019)
Organic additives are recently being used in animal diets owing to their ability to control metabolic issues and result in better animal performance. Specifically, the organic additive Fator P ® presents an additional advantage that is to cause a lesser greenhouse gas emission. This study evaluated whether Fator P ® intake changes ruminal parameters or animal performance of beef cattle. Evaluations were carried out in a feedlot experiment divided into growing (46 days; two diets [control mix—CM and standard mix—SM] and finishing (lasted 83 days; four diets: CM, SM, Fator P ® + virginiamycin, and Fator P ® alone [FP]) trials. Animal performance study involved 48 animals allocated to 12 collective pens in completely randomized experimental design. Ruminal parameters were evaluated in separate metabolism study developed carried out using individual pen with four steers. During growing trial, FP diet resulted in higher (p < 0.05) dry matter intake (DMI) and ruminating time. In the finishing trial, diets containing Fator P ® resulted in higher DMI than obtained with CM. Most of the ruminal parameters did not differ (p > 0.05) among dietary treatments. Therefore, Fator P ® represents a viable and safe strategy for supplementation to beef cattle finished using high-concentrate diet in feedlot systems.
Keywords: average daily gain; digestibility; growth promotants